Multicultural Workshops and Inclusion of Roma Students in Primary Education (Annual of the Faculty of Philosophy in Skopje, 2025)
The Multicultural Workshops program was launched with an intention to enablestudents from different ethnic backgrounds to interact with each other through collaborativejoint activities designed to provide conditions for learning from each other about eachother’s culture.This paper presents the results from a quantitative pre- and post- intervention studycarried out in two turns in one ethically mixed primary school where Roma students attendclasses in Macedonian as a language of instruction. The participants were 58 ethnicMacedonian and 63 ethnic Albanian students from four age groups who took part in 12-15Multicultural Workshops that included Roma students. In order to assess the effects of theexposure to the workshops on their perception of Roma, all participants were given a custom-designed instrument to identify the degree of social distance, trust and stereotypes towardsthem, as well as group anxiety and willingness for positive action.Taking into account the results that show differences in the participants’ perceptionof Roma and in their readiness to interact with them before and after the program, thepaper concludes that, under defined conditions, this approach could be considered as an exampleof a good practice in integrating Roma students in primary education.
Keywords: INCLUSION; MULTICULTURAL WORKSHOPS; ROMA STUDENTS